(3GdOdGFd aj eYGfi GdMOjKs - (3GdSQbSWjs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hbGd ai MOjK GdfHi Udi Gddg Ydjg hSde Cfg CJi HYdGdg TGg bhdg HYdGdg TGg s
(3BNQgG (B:s
(3Ke JQhi dHfkG hSefkG hScQkG hCgd GdTGe jJNPhf ced cJGH GdOdGFd Ydi eYGfi ai GdMOjK s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs